Omamori dalam Kepercayaan Masyarakat Jepang - Yuliani Rahmah (Diponegoro University, 2019)
(Omamori in Japanese Belief ) Omamori known as one of animisn and pantheism`s tradition. Omamori, which has been known since the Tokugawa period, still exist in modern Japanese society as a talisman. Theres some questions about what and how the shape of this Japanese charm is. By using literature study approach this article will describe the existence of omamori in Japanese beliefs which includes the definition, form and type of omamori. Omamori is spiritual charms, talismans and amulets in the Japanese religious tradition that possess the power to ward off misfortune and procure good luck. They can be made of pieces of wood, patches of cloth, strips of paper or rings of metal, and come in various sizes. There are seven types of omamori which are most used by Japanese people. That seven types of omamori are used as protective charms for each stage of the human life cycle.